Retención de los sellantes de fosas y fisuras como método preventivo de caries en niños y niñas de 5 a 12 años, revisión sistemática de la literatura (2021)
Pit and fissure sealants are characterized by the protection of the chewing surfaces in temporary or permanent molars and premolars, thus preventing the contact of bacterial plaque or microorganisms as the causal agent.